Improved performance of perylene-based photovoltaic cells using polyisocyanopeptide arrays - Foster, Sam; Finlayson, Chris E.; Keivanidis, Panagiotis E.; Huang, Ya Shih; Hwang, Inchan; Friend, Richard H.; Otten, Matthijs B.J.; Lu, Li Ping; Schwartz, Erik; Nolte, Roeland J.M.; Rowan, Alan E. (My University, 2009)
Photovoltaic devices incorporating perylene-substituted polyisocyanide materials have been demonstrated, using blend systems with polythiophene- and polyfluorene-based conjugated polymers. Prototypical structures with nominal (1:1) blend weight ratios of the polyisocyanide with poly(3-hexylthiophene) (P3HT) and poly(9,9'-dioctylfluorene-co-bis(N,N'-(4-butylphenyl))-bis(N,N'- phenyl)-1,4-phenyldiamine) (PFB) readily showed an order of magnitude improvement in power conversion efficiency, as compared to analogous blend architectures using a perylene (PDI) monomer, whereas the performance of strongly phase-separated F8BT (poly(9,9- dioctylfluorene-co-benzothidiazole) blend devices showed no such improvement. We propose that the use of polyisocyanide chains as a molecular template offers a method by which the morphology and connectivity of photovoltaic blends can be modified and enhanced. © 2009 American Chemical Society.
Keywords: Hydrocarbons; Thin films; Organic polymers; Photovoltaics; Aromatic compounds